Nujiangexanthone A Inhibits Hepatocellular Carcinoma Metastasis via Down Regulation of Cofilin 1 - Zhang, Li; Chai, Zongtao; Kong, Siyuan; Feng, Jiling; Wu, Man; Tan, Jiaqi; Yuan, Man; Chen, Gan; Li, Zhuo; Zhou, Hua; Cheng, Shuqun; Xu, Hongxi (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) is one kind of malignant tumors with poor prognosis. High expression level of cofilin 1 (CFL1) has been found in many types of cancers. However, the role of CFL1 in HCC hasn’t been known clearly. Here, we found that CFL1 was up regulated in human HCC and significantly associated with both overall survival and disease free survival in HCC patients. Nujiangexanthone A (NJXA), the caged xanthones, isolated from gamboge plants decreased the expression of CFL1, which also inhibited the migration, invasion and metastasis of HCC cells in vitro and in vivo. Down regulation of CFL1 inhibited aggressiveness of HCC cells, which mimic the effect of NJXA. Mechanism study indicated that, knockdown of CFL1 or treatment with NJXA increased the level of F-actin and disturbed the balance between F-actin and G-actin. In conclusion, our findings reveal the role of CFL1 in HCC metastasis through the CFL1 / F-actin axis, and suggest that CFL1 may be a potential prognostic marker and a new therapeutic target. NJXA can effectively inhibit the metastasis of HCC cells by down regulating the expression of CFL1, which indicated the potential of NJXA for preventing metastasis in HCC.